Demographic Profile of the Internet-Using Population of India. (November 2014) - Varshney, Bharti; Kumar, Prashant; Sapre, Vivek; Varshney, Sanjeev
The study seeks to investigate the Internet usage habits among the online population in India. It intends to confirm if respondents differed on the basis of demographic variables such as age, gender, occupation and city/town tier. Based on primary research, the present study examines the differential effects of demographic variables on various online activities, their usage frequency and duration. The study proposes a possible segmentation of Internet users and a classification of Internet activities. K -mean cluster analysis and one-way analysis of variance (ANOVA) have been used to capture the same. The results suggest that activity-wise usage and duration of Internet usage vary with age, occupation and city/town tier of the respondents, but not much with gender. The factor analysis suggested grouping the dependent usage and activity variables into five major factors. The article would be helpful for the Internet service providers in segmenting the Internet users and enhancing the scholars' understanding of effect of given demographic variables on Internet usage.